Recent Advances in Synthesis of Benzoxazole - Bansal, Shivani (Mini-Reviews in Organic Chemistry, 2021)
Benzoxazoles are an important class of the heterocyclic compound and display a wide range of pharmacological activities and other applications. Due to their varied application, they are always an important moiety for synthetic chemists to develop newer methodologies for their synthesis. In this review, an attempt has been made to briefly describe and summarize all of the available methods for the preparation of benzoxazoles, and their substitutes as well as also discuss their functionlization.
Keywords: 2-Aminophenol